Using Reflective Journal Writing to Develop Undergraduates’ Metacognitive Awareness in ESL Writing - Muhammad Mukhtar Aliyu; Mohammed Sani Ya'u; Halima Sadiya Yakubu; Yusuf Muhammad Jika; Ahmed Tanimu Jibril (ELT Forum: Journal of English Language Teaching, 2023)
Studies have shown that many undergraduates face various challenges in ESL writing, especially academic writing. Most of the students lack the basic knowledge and skills required for them to achieve their writing task which is known as metacognition. Therefore, this study employs a reflective journal writing strategy to develop undergraduates’ awareness of metacognition in ESL writing. The study adopts a pre-and-post quasi-experimental research design with an intact class of (87) third-year undergraduates in a creative writing class. The study employed two instruments for the data collection: a writing task and a metacognitive questionnaire. Both instruments were used before and after the reflective journaling for 12 weeks. The pre-and post-test mean scores of the two instruments were compared using a paired-sample t-test. The results of the study show a significant improvement in the participants’ metacognitive awareness level and writing skills after writing the reflective journals. The study makes some recommendations for further studies and practice.